219k views
3 votes
Find the product.
(2² + b) (a²-9b)

User Rgcb
by
5.5k points

1 Answer

5 votes

Answer:

Step-by-step explanation:(2^2+b)(a^2-9b)

This means to expand the brackets

2^2=4

(4+b)(a^2-9b)

Look at the first bracket

The first term is 4 and is multiplied by the second bracket

4(a^2-9b) expand the brackets

=4a^2-36ab

and

The second term of the first bracket is:

b(a^2-9b)=a^2(b)-9b^2

We now add the two expanded brackets together to get the following:

=4a^2-36ab+a^2-9b^2

cannot be simplified any further

User Rishav Rastogi
by
4.7k points